Participation and project sustainability : Participatory Integrated Development in Rain-fed Areas (PIDRA) project in East Java-Indonesia : a thesis presented in partial fulfilment of the requirement for the degree of Master of Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Komalawati (Massey University, 2008)
This thesis examines the relationships between participation and project sustainability. By using the Participatory Integrated Development in the Rain-fed Areas (PIDRA), an integrated rural development project, in three districts of East Java, Indonesia, as a case study, it addresses the question about what kind of participation will lead the intended beneficiaries to continue to use and benefit from the services that remain beyond the project period. The research found that the project mostly targeted the poor, marginalised, and vulnerable people, and widows as household heads. However, some high school graduates and wealthy villagers were also included as target beneficiaries. Most participants were actively involved and participated in the project implementation activities, but rarely participated in project planning and design as well as monitoring and evaluation. The results also show that factors influencing participation of the intended beneficiaries of the PIDRA Project in the target areas were: the responsibility of the beneficiaries to the groups as members and as leaders part of the management team; the level of education, knowledge, and skills of participants; incentives provided to access credits; the availability and use of sanctions; the geographical situation; poverty; age; support from the government; and the role of facilitators. Analysis of the case study shows that the PIDRA Project in East Java will likely have some sustainable activities and benefits in the short term. Furthermore, participation is likely lead to the project sustainability of some project elements when participation is not only used as a means but also as an end. However, the results also suggest the increasing cooperation and collaboration of government and the NGOs, and defining participant groups based on similar educational background and socio-economic situation will enhance participation and project sustainability. This study would also raise the attention of development practitioners of the dangers of the participatory approach in their practice because it could be manipulative, harm people who are supposed to be advantaged, and hence create “new tyranny” in development interventions.
Keywords: Rural development; Community participation; Project sustainability; Fields of Research::370000 Studies in Human Society::370400 Human Geography::370404 Economic geography